Analisis Konsep Penerimaan Diri dalam Buku Seni Memahami & Menerima Diri - Muhammad Candra Wijaya; Masduki Asbari; Muhamad Abdul Robi (Yayasan Aya Sophia Indonesia, 2025)
This study aims to provide an in-depth analysis of the main concepts of self-acceptance presented in Aba Mehmed Agha’s book The Art of Understanding & Accepting Yourself. The book offers a reflective approach that integrates psychological and spiritual perspectives to help individuals understand their inner dynamics and the thought patterns that shape their lives. In his work, Agha emphasizes that self-acceptance is not merely a rational process but also an emotional journey that requires the courage to confront one’s personal reality as it truly is. This research employs a qualitative descriptive method through comprehensive reading and thematic categorization of the central ideas found throughout the book. These ideas are then analyzed within the framework of modern psychological theories, particularly those related to self-awareness, emotion regulation, and healing from past emotional wounds. The findings indicate that the process of accepting oneself can help individuals release external pressures, improve intrapersonal harmony, and discover a more authentic sense of meaning in life. Therefore, the book provides an important contribution to the development of applicable self-acceptance concepts within the context of mental health and personal growth in the modern era.